(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The article looks at Theodore Roszak’s The Memoirs of Elizabeth Frankenstein from the perspective of an attempt at privileging female narrative voice, largely overlooked in Mary Shelley’s original. It is argued that despite noble aims the author’s reliance on stereotypical binaries (man-science/woman-nature) effectively silences the developments of significant strains of feminist critical discourses. Such an approach - together with exploring the otherwise reversed, but still biased binary male/female oppositions - accounts for an ineffective attempt at (re)creation of female experience.